Did Economic Inequality Cause the Economic Crisis - Šuković, Danilo (Panoeconomicus, 2014)
The sudden and large increase of interest in questions of distribution of wealth and economic inequality, arising in recent years, resulted primarily from the enormous increase in inequality that occurred during the last three decades. The global economic crisis that emerged in 2008 gave a new impetus to this research because numerous scientific studies appeared in which inequalities were given as one of the key causes of the crisis from which the world is slowly recovering. This is especially true in Europe, whose recovery is barely discernible. This paper analyzes the trends of economic inequality and points to the impact of inequality on economic growth. The central question in this paper, however, is whether the economic inequalities caused the economic crisis. Although opinions differ as to inequality’s impact on the occurrence of the crisis, the fact is that enormous economic inequalities, and especially their permanent growth, could have many negative effects, such as increasing poverty, increasing social stratification and causing global economic crises. As many authors have pointed out, escalating inequality is not an inevitable price of progress. On the contrary, it is a political decision that often has expensive ramifications. Key words: Economic inequality, Income, Economic growth, Crisis, Gini coefficient. JEL: D31, D63, F63, G01.